Analysis on Cost Efficiency Impact in PT XYZ ADKAR and HERO Theory - Miscel, Miscel; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2013)
Today the world of telecommunications experience intense competition, not only for the operators but also for vendors and suppliers. Competition tariff making operators also reduce the cost of network devices and service / maintance. It affects all network equipment providers or vendors. Each vendor trying to offer competitive prices for the operator. Yet the competition among vendors themselves. PT XYZ as one of the network equipment providers strive to remain competitive and survive in the situation. One attempt was made by PT XYZ is a cost efficiency program within the company as a whole. Cost efficiency program seeks to reduce operating costs in the company so that it can remain competitive in the world of telecommunications. Cost efficiency program includes several things and involve benefits in PT XYZ. Cost efficiency program is an example of change management in the form of a company. And of course it will have an impact on its employees. Cost efficiency program will have an impact on the performance of the employees of PT XYZ. Therefore, this thesis aims to analyze the impact of cost efficiency with Adkar and HOPE theory. The analysis undertaken will focus on Adkar used as an indicator of phase change and HOPE theory is used to assess the extent to which energy and positive aura within XYZ employees.Â Key words : cost efficiency, adkar theory, hero theory, performance of work